THE EFFECTIVENESS OF ARTIFICIAL INTELLIGENCE CHATBOTS TO IMPROVE ENGLISH LANGUAGE LEARNING - Sander, Abdurrasyiid Alaik (SIMPLE: International Journal of English Education, 2024)
Artificial Intelligence (AI), particularly chatbots, has emerged as a transformative tool in English Language Learning (ELL). As educational technology evolves, AI's capacity to enhance traditional teaching methods has garnered considerable interest. This research explores the integration of AI chatbots as interactive tools aimed at enhancing language skills, fostering student engagement, and assisting educators in delivering personalized instruction. Through a comprehensive literature review, this study examines existing insights and perspectives on the use of chatbots in education. The findings highlight significant benefits in vocabulary acquisition, grammatical proficiency, and student motivation. Moreover, the study identifies challenges such as infrastructure requirements and ethical considerations. This research contributes to the growing body of knowledge on AI in education, offering insights to inform effective integration strategies and future research directions.